Composition, origin, and potential industrial applications of REEs-rich authigenic kaolinite separated from the Lower Cretaceous white sands, Saudi Arabia - Aljabbab, Abdulrahman; Qadrouh, Ayman N.; Alajmi, Mamdoh S.; Alotaibi, Abdulrahman M.; Baioumy, Hassan; Alyousif, Mazen M.; Bin Rogaib, Abdulrahman M.; Fal, Mokhtar; Alkhammali, Sultan A. (Frontiers in Earth Science, 2025)
The white sands from the Cretaceous Biyadh Formation, Saudi Arabia, are exploited as a raw material for the glass sand industry and contain approximately 15 wt% kaolinite. SEM reveals that the kaolinite develops as a blocky, pore-filling cement of euhedral, pseudo-hexagonal plates ranging from 5 to 10 µm in width and from 10 to 20 µm in length, suggesting its authigenic origin during the late diagenesis. Anatase occurs as very fine grains interspersed among the kaolinite flakes. The authigenic kaolinite is associated with remarkably high concentrations of rare earth elements (REEs) (average 1,126 ppm), Zr (average 1,133 ppm), and Li (average 187 ppm). REEs occur as the phosphate phase, while Zr is associated with the anatase, and Li is hosted by kaolinite. These high concentrations are probably due to the enrichment of these elements during the diagenesis of the studied kaolinite. Alteration of the source minerals during periods of subaerial exposure and/or at shallow burial depths due to meteoric water influx is deduced as a possible mechanism for the formation of the studied kaolinite. The supergene origin of the kaolinite is confirmed by the relatively high concentrations of Ti and Ce + Y + La. The geochemistry and large crystal size suggest the potential application of the kaolinite in paper coating and as a filler. While the high Al2O3 and low SiO2 contents suggest its potential application in super-standard porcelain and sanitary ware, partial removal of TiO2 will allow its application in the pharmaceutical and cosmetics industries. Additionally, REEs, Zr, and Li can be separated from the white sands as valuable byproducts, along with the kaolinite.